Apremilast Was Associated with an Acceptable Safety Profile in ESTEEM Trials - Rizzo, Toni (MD Conference Express, 2014)
Two phase 3 randomized controlled trials were performed to evaluate the safety and efficacy of oral apremilast (CC-10004) in patients with moderate to severe plaque psoriasis. This article discusses the safety analysis from the pooled data of the ESTEEM 1 [NCT01194219] and ESTEEM 2 trials [NCT01232283].